Oxide minerals in the granitic cupola of the Jalama Batholith, Salamanca, Spain. Part I: accessory Sn, Nb, Ta and Ti minerals in leucogranites, aplites and pegmatites - Llorens,T.; Moro,M.C. (Journal of Geosciences, 2012)
Sn-Nb-Ta-Ti oxides occur as accessory minerals in the granitic facies of the External Unit in the Jalama Batholith (Salamanca, Spain) and in the related LCT pegmatite dikes of the rare-element class. Moreover, abundant cassiterite and columbite-group minerals crystallized in the Cruz del Rayo peribatholithic pegmatite dikes, cutting the pre-Ordovician low-grade metasedimentary rocks of the surrounding Schist-Graywacke Complex.Cassiterite, rutile, ilmenite and tantalite-(Fe) occur disseminated in the border facies of the External Unit, especially throughout the tourmaline-bearing leucogranite and the apical aplites. Additionally, cassiterite, rutile and Ta-rich rutile developed locally in the intragranitic pegmatite dikes. Two types of peribatholithic pegmatites can be distinguished at Cruz del Rayo: (i) granite-like pegmatites, with columbite-(Fe) I and II and cassiterite, in which the influence of metasomatic fluids led to formation of the late albite unit and crystallization of tantalite-(Fe), and (ii), greisen-like bodies, which contain high amounts of columbite-(Fe), columbite-(Mn), tantalite-(Mn) I and II as well as cassiterite. The primary oxide assemblage in both types of the peribatholithic pegmatite dikes would have crystallized as a result of magmatic differentiation of the residual melts coming from the Jalama granitic cupola. However, crystallization of the secondary assemblage, richer in Fe and Ta, is interpreted mainly as a consequence of interaction with external fluids coming from the metamorphic host rocks, more or less mixed with meteoric fluids, although partial dissolution and re-precipitation could also have played an important role, as well.
Keywords: Jalama Batholith; pegmatite dikes; cassiterite; columbite-group minerals